A72 NON-INVASIVE PREDICTION OF ESOPHAGEAL VARICES BY TRANSIENT ELASTOGRAPHY AND PLATELET COUNT IN PATIENTS WITH HEPATITIS B AND ADVANCED CHRONIC LIVER DISEASE: VALIDATION OF BAVENO VI AND EXPANDED BAVENO VI CRITERIA. (4th March 2021) - Zoughlami, A; Serero, J; Sebastiani, G; Deschenes, M; Wong, P; Khan, A Q
Abstract: Background: Patients with compensated advanced chronic liver disease (cACLD) are at higher risk of developing complications from portal hypertension, including esophageal varices (EV). Baveno VI and expanded Baveno VI criteria, based on liver stiffness measurement (LSM) by transient elastography combined with platelet count, have been proposed to avoid unnecessary esophagogastroduodenoscopy (EGD) screening for large esophageal varices needing treatment (EVNT). This approach has not been validated in patients with chronic hepatitis B virus (HBV) infection, who have etiology-specific cut-off of LSM for liver fibrosis. Aims: We aimed to validate the Baveno VI and expanded Baveno VI criteria for EVNT in HBV patients with cACLD. Methods: We performed a retrospective analysis of HBV patients who underwent LSM in 2014–2020. Inclusion criteria were: a) diagnosis of cACLD, defined as LSM > 9 kPa; b) availability of EGD and platelets within 1 year of LSM. Baveno VI (LSM <20 kPa and platelets >150, 000) and expanded Baveno VI criteria (LSM <25 kPa and platelets >110, 000) were tested for EGD sparing. Diagnostic performance of these criteria against gold standard (EGD) was computed and compared to patients with hepatitis C virus (HCV) infection and nonalcoholic steatohepatitis (NASH) etiologies, where these criteria have been widely validated. In these patients, the threshold for cACLD definition was >10 kPa. Results: A total of 287 patients (mean age 56, 95% Child A) were included, comprising of 43 HBV (58% on antiviral therapy), 134 HCV and 110 NASH patients. The prevalence of any grade EV and EVNT was 25% and 8% in the whole cohort, with 19% and 5% in HBV patients, respectively. Table 1 reports diagnostic performance, spared EGD and missed EVNT according to non-invasive criteria and cACLD etiology. Both Baveno VI and expanded Baveno VI criteria performed well in patients with HBV-related cACLD. There was no significant difference on diagnostic performance of these non-invasive criteria across the cACLD etiologies. Conclusions: These results support use of non-invasive criteria based on LSM and platelets to spare unnecessary EGD in patients with HBV and cACLD. Baveno VI and expanded Baveno VI criteria can improve resource utilization and avoid invasive testing in context of screening EGD for patients with HBV-related cACLD. Funding Agencies: None